ISLAM DAN PENGUATAN CIVIL SOCIETY DI INDONESIA - Besse Tenriabeng Mursyid (Qaumiyyah: Jurnal Hukum Tata Negara, 2020)
The idea and strengthening of civil society praxis is an alternative model for the struggle towards democratization. In Indonesia, efforts to strengthen civil society cannot be separated from Islam as the religion practiced by the majority of the Indonesian population. Efforts to strengthen civil society cannot ignore religious factors, especially Islam. In fact, in certain cases the existence of Muslims who are inspired by Islamic teachings is the basis for socio-cultural and even political change in Indonesia. The potential of Islamic teachings, which contain elements of beliefs and norms and ethical teachings related to the socio-cultural community practiced by Indonesian Muslims, are very large in determining the socio-cultural format of society. Likewise, in the effort to strengthen civil society, Muslims occupy a leading position which can be expected to be a counterweight to the country's dominant tendency. In other words, quantitatively, Muslims based on Islamic teachings have a prerequisite for the growth and strengthening of civil society in Indonesia. Islam as a religion that is embraced by the majority of Indonesians is a solid foundation in encouraging the strengthening of civil society in Indonesia.